A Handshake From Antimicrobial Stewardship Opens Doors for Infectious Disease Consultations. (10th February 2017) - Messacar, Kevin; Campbell, Kristen; Pearce, Kelly; Pyle, Laura; Hurst, Amanda L.; Child, Jason; Parker, Sarah K.
Abstract: Implementation of a unique in-person pediatric antimicrobial stewardship program was associated with a significant increase in infectious disease consultations at a quaternary care children's hospital. This study demonstrates that antimicrobial stewardship programs support, and do not compete with, infectious disease programs.